2005
DOI: 10.1021/jm058162z
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolo[1,5-a]pyrimidines:  Estrogen Receptor Ligands Possessing Estrogen Receptor β Antagonist Activity.

Abstract: The caption of Figure 7 incorrectly suggests that Sprague-Dawley rats were used in studies of HPA activation. Studies of HPA activation were performed using CD-1 mice (as described everywhere else in the manuscript).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(40 citation statements)
references
References 0 publications
2
37
0
1
Order By: Relevance
“…The selectivity of these drugs for one receptor subtype over the other have been previously demonstrated by others (Compton et al 2004;Frasor et al 2003;Harrington et al 2003, Kraichely et al 2000Meyers et al 2001, Stauffer et al 2000Sun et al 2002Sun et al , 2003. The effective doses of PPT, DPN and MPP that significantly modulated PPI or startle in the present study (see Results section), are also known to be equivalent to doses of E2 or estradiol benzoate (EB) previously shown to affect uterine weight or behavioral readouts (Harris et al, 2002;Lynch et al, 2014;Santollo and Eckel, 2009).…”
Section: Drug Preparation and Administrationsupporting
confidence: 82%
See 1 more Smart Citation
“…The selectivity of these drugs for one receptor subtype over the other have been previously demonstrated by others (Compton et al 2004;Frasor et al 2003;Harrington et al 2003, Kraichely et al 2000Meyers et al 2001, Stauffer et al 2000Sun et al 2002Sun et al , 2003. The effective doses of PPT, DPN and MPP that significantly modulated PPI or startle in the present study (see Results section), are also known to be equivalent to doses of E2 or estradiol benzoate (EB) previously shown to affect uterine weight or behavioral readouts (Harris et al, 2002;Lynch et al, 2014;Santollo and Eckel, 2009).…”
Section: Drug Preparation and Administrationsupporting
confidence: 82%
“…DPN and PHTPP show a 70--and 36--fold selectivity, respectively, for ER--β over ER--α (Compton et al 2004, Meyers et al 2001). All ER--ligands used in the present study have previously been shown to reach the brain and exert central effects in rodents (Dillon et al, 2013;Grassi et al 2013;Harris et al 2002;Lund et al 2005;Saleh et al, 2013;Santollo and Eckel, 2009;Santollo et al 2007Santollo et al , 2010.…”
Section: Introductionmentioning
confidence: 94%
“…daily with 2 mg PHTPP (TOCRIS) (12) diluted in ethanol at a final concentration of 100 mM. PHTPP was incubated at 37˚C before further dilution in RPMI 1640.…”
Section: Treatment With Phtpp and Indazole-clmentioning
confidence: 99%
“…New series of isoxazolines has been synthesized and has shown moderate antimicrobial activity 59 [70]. Pyrimidine analogues: N-fused analogues of chalcones particularly pyrimidines have received augmented interest due to their plethora of biological actions such as antifungal [71], antibacterial [72], antitumor [73], analgesics [74], anti-inflammatory [75], anti-trichomonal [76], KDR kinase inhibition [77], CRF-1 receptor antagonists [78,79] estrogen receptor ligands, and COX-2 selective inhibition [80]. Sharma et al synthesized a series of quinolinyl chalcones and quinolinyl pyrimidines and screened them against M. tuberculosis and NF-54 strains of P. falciparum among all compounds with 4-amino linkage showed promising activity against NF-54 strains of P. falciparum.…”
Section: Analogues Of Chalcones Pyrazoline Analogues With Various Phamentioning
confidence: 99%